Induced ruminative and mindful self-focus in daily life across the menstrual cycle in women with and without premenstrual dysphoric disorder - Nayman, Sibel; Schricker, Isabelle; Grammatikos, Ioanna Franziska; Reinhard, Iris; Kühner, Christine (Behaviour research and therapy, 2024)
Rumination and mindfulness are transdiagnostic risk and protective factors while their role in Premenstrual Dysphoric Disorder (PMDD) is unclear. Thus, we aimed to investigate the cycle-phase-specific effects of rumination and mindful self-focus on momentary mood and cognitions in women with and without PMDD. This study involved brief ambulatory inductions of ruminative and mindful self-focus along with ambulatory assessments of negative (NA) and positive affect (PA), and rumination, present-moment-awareness (PMA) and self-acceptance on two days during both the follicular and late luteal phase in women with and without PMDD (n = 60 each). Compared to healthy controls, women with PMDD showed stronger increases in PA in response to mindful self-focus inductions during the late luteal phase, whereas no such group differences were identified during the follicular phase. Independent of clinical status and cycle phase, induced ruminative self-focus immediately increased momentary NA and rumination and decreased PMA, whereas induced mindful self-focus inductions increased momentary self-acceptance. Overall, higher PA-reactivity toward mindful self-focusing during late luteal phase in women with PMDD points to the potential of cycle-phase-specific mindfulness interventions for PMDD. Irrespective of cycle phase, rumination and mindfulness appear to represent targets for brief prevention and intervention measures for both non-clinical and clinical groups.